The Politics of Disability Law in Indonesia: Transformation to Strengthen the Rights of Persons with Disabilities - Akhmad Kamil Rizani; Kharlie, Ahmad Tholabi; Pelu, Ibnu Elmi Acmad Slamat; Tarantang, Jefry; Muchimah; Farhana, Nyimas Tasya (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
This article discusses the legal politics of legal transformation for persons with disabilities in Indonesia. The Indonesian nation has always recognized and guaranteed respect for human dignity, including persons with disabilities. This can be seen in Law No. 4 of 1997 on Persons with Disabilities, which explains the government's efforts to protect the rights of persons with disabilities by focusing on rehabilitation, providing social assistance, and maintaining social welfare. However, the text content in the law still adheres to a charity-based paradigm, so it has not been able to handle and ensure equal opportunities for persons with disabilities. The method used in this research is normative juridical with primary legal materials Law No. 19 of 2011 concerning the Ratification of the Convention on the Rights of Persons with Disabilities and Law No. 8 of 2016 concerning Persons with Disabilities through a legislative and historical approach. The results of this study show that the legal politics of the formation of Law No. 8 of 2016 on Persons with Disabilities shows the realization of participatory democracy. The transformation of the law changes the paradigm from charity-based to human rights-based, which better guarantees the protection, promotion, and enforcement of the rights of persons with disabilities. Public education on the rights of persons with disabilities, the development of disability-friendly infrastructure, and increased participation of persons with disabilities in decision-making are important for implementation.